Genome-Wide Analysis of MADS-Box Genes in Foxtail Millet (Setaria italica L.) and Functional Assessment of the Role of SiMADS51 in the Drought Stress Response - Zhao, Wan; Zhang, Li-Li; Xu, Zhao-Shi; Fu, Liang; Pang, Hong-Xi; Ma, You-Zhi; Min, Dong-Hong (Frontiers in Plant Science, 2021)
MADS-box transcription factors play vital roles in multiple biological processes in plants. At present, a comprehensive investigation into the genome-wide identification and classification of MADS-box genes in foxtail millet has not been reported. In this study, we identified 72 MADS-box genes in the foxtail millet genome and give an overview of the phylogeny, chromosomal location, gene structures, and potential functions of the proteins encoded by these genes. We also found that the expression of 10 MIKC-type MADS-box genes was induced by abiotic stresses (PEG-6000 and NaCl) and exogenous hormones (ABA and GA), which suggests that these genes may play important regulatory roles in response to different stresses. Further studies showed that transgenic Arabidopsis and rice plants overexpressing SiMADS51 had reduced drought stress tolerance as revealed by lower survival rates and poorer growth performance under drought stress conditions, which demonstrated that SiMADS51 is a negative regulator of drought stress tolerance in plants. Moreover, expression of some stress-related genes were down-regulated in the SiMADS51-overexpressing plants. The results of our study provide an overall picture of the MADS-box gene family in foxtail millet and establish a foundation for further research on the mechanisms of action of MADS-box proteins with respect to abiotic stresses.